Effectiveness of an Educational Booklet for the Management of Patients with Chronic Low Back Pain (Medicine Today, 2023)
Introduction: The aim of the present study was to assess the effectiveness of provision of an educational booklet for the management of patients with chronic low back pain.Material and Methods: A Randomized controlled clinical trial was conducted from January 2018 to June 2018 among 80 patients attending at Physical Medicine and Rehabilitation outpatient department of the Shaheed Suhrawardy Medical College and Hospital after obtaining requisite consent from the patients. 80 Patients were divided into two groups (Group A and Group B). Group A contains Patients educational booklet group + exercises + analgesics (Case group). Group B contains Physicians advice only group + exercises + analgesics (control group). Data were collected through interviewing and examining of the patients. The collected data were entered into the computer and analyzed by using SPSS (version 20.1) to assess the effectiveness of provision of an educational booklet for the management of patients with chronic low back pain. The study was approved by the institutional ethical committee.Results: In a pool of 80 patients, the range of age was 18-55 years in case group and control group. There was no significant difference found in age between case and control group (p value is 0.383). Among the patients of case group 28 (70.0%) were male and 12 (30.0%) were female. Among the patients of control group 17 (42.5%) were male and 23 (57.5%) were female. Visual analogue score (VAS) score of group A patient was 5.4±1.0 and group B was 5.7±1.1 (p=0.143). At the first follow up the mean VAS score of group A was 4.5±1.0 and group B was 4.8±0.9 (p=0.111). At the second follow up the mean VAS score of group A was 3.1±0.9 and group B was 3.5±0.8 (p=0.077). And at the final (third) follow up the mean VAS score of group A was1.9±0.8 and group B was 2.4±0.6 (p=0.002).Conclusion: There was significant improvement of pain of case group than control group. At the end of study we can tell that, educational booklet is effective for the management of patients with chronic low back pain.Medicine Today 2023 Vol.35(2): 87-90